An error analysis of using simple past tense on student's writing recount text - Faizah, Iis; Widianto, Muhammad Wahyu; Lestari, Maria Yosephin Widiarti (Universitas Aki, 2025)
Doing error analysis can be one of the best ways to determine and to provide information of student needs in learning process. This research aimed to identify and to describe the causes of error in using simple past tense found in student’s recount text production. In this research, the researcher used descriptive and qualitative research. For collecting data, the writer used students’ writing recount text test of tenth grade students of SMA N 1 Mranggen. From the analysis, it was found that students did all types of error. the total of students’ error were 167-word errors from 34 texts. It was classified into four types of error. Those were omission with 87 errors (52,09%), misformation with 67 errors (40,11%), addition with 67 errors (4,2%), and misordering with 5 errors (3,6%). The researcher also found that the most common and the most dominant types of error in using simple past tense is omission type with 87 errors (52,09%) of total errors under the categorization of irregular past. In this case the researcher found as many as 21 errors or 10, 16% in omission of irregular past based on caused of error namely Interlingual and Intralingual cause of error.